PENGENALAN EMOSI PADA ANAK TK HAPPY HOLY KIDS MALANG DENGAN EMOTIONAL CUP - Jannati, Sabila; Ningsih, Dwi Rahayu; Zahro, Amanda Halimatuz; Maharani, Kezya Putri; Wiyanto, Yehezkiel Sheva Putra (Universitas Negeri Malang, 2024)
Emotions are an important part of human life. Since birth, humans have had various emotions, such as happy, sad, angry and afraid. The standard for recognizing emotions is at the age of 5-6 years. However, in reality, not all Happy Holy Kids Malang Kindergarten children recognize their own emotions. The aim of this community service is to introduce basic emotions to Happy Holy Kids Malang Kindergarten children. The method for recognizing emotions is through education using emotional cup media. The result of this community service is that Happy Holy Kids Kindergarten children can recognize and understand the basic emotions that they need to recognize. They can talk about the emotions they have felt or are currently feeling. Suggestions for the next community service, you can use more interesting media. If you still use an emotional cup, then it should be made even more interesting and with more varied emotions.